(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The development of ethnocultural competence has become a significant priority in contemporary teacher education due to the increasing influence of globalization, multicultural interaction, and educational internationalization. Future teachers are expected to possess not only professional and pedagogical competencies but also the ability to understand, respect, and effectively engage with representatives of diverse cultural and ethnic communities. The relevance of this study lies in the need to improve pedagogical approaches that facilitate the systematic development of ethnocultural competence among pre-service teachers. The purpose of this research is to examine the theoretical and practical aspects of enhancing an integrative modular approach to ethnocultural competence development in teacher education. The study focuses on identifying effective pedagogical conditions, methodological principles, and educational strategies that contribute to the formation of intercultural awareness, cultural sensitivity, and professional readiness for multicultural educational environments. The research is based on competence-based, cultural, interdisciplinary, and learner-centered approaches. The findings indicate that the integrative modular approach provides a comprehensive framework for combining ethnopedagogical knowledge, intercultural communication skills, reflective learning practices, project-based activities, and digital educational technologies. The implementation of this approach contributes to the development of cultural identity, tolerance, intercultural dialogue, and professional adaptability among future teachers.